FORMULASI GEL EKSTRAK BUAH TOMAT DAN BENZOFENON SERTA UJI NILAI SPF - lidia lidia (Jurnal Penelitian Farmasi Indonesia)
The research of formulation gel preparation combination tomato extract (Solanum lycopersicum L.) and benzophenone. The research to know that the combination of tomato extract and benzophenone can be formulated into gel preparation with variation concentration carbopol 940 0,5%, 1%, and 1,5% as gel base. Then gel was evaluated, include observation of organoleptic, homogeneity, pH, viscosity, spreadability, freeze thaw test, iritation test, and for the most stable formula was determined SPF value by measuring absorbance sample at wavelength 290–320 nm with interval 5 nm using UV-Vis spectrophotometry. Results of the research showed that gel preparation of second formula was the most stableof the three with a typical smell tomato, yellow color, semisolid consistence, homogeneous, pH 5.73 ± 0.05, viscosity 4533 ± 115.47 cPs, has good spreadability, not irritating, and has SPF value28.61 ± 0.01.